Assessment of Pharmacist Led Patient Counseling Program for Hypertension Management: The Transformative Role of Community Pharmacies in Chronic Disease Management - Madeeha Malik; Usman Aslam; Azhar Hussain; Ayisha Hashmi (International Journal of Innovative Research in Medical Science, 2021)
Background: Effective management of hypertension depends on efficacy of therapy as well as patient adherence to medication therapy and non-pharmacological approaches. As one of the important member of primary healthcare team, community pharmacists can play a key role in counseling patients and managing their chronic illnesses. Aim: The objective of the study was to assess the effectiveness of pharmacist counseling on management of hypertension of patients attending community pharmacies in twin cities of Pakistan. Methodology: A randomized, controlled, single blinded, pre-post intervention study design was used. Pharmacists working at community pharmacies included in group A (intervention) were targeted for training while no training was given to the pharmacists working at community pharmacies included in group B (control). The total numbers of patients were 40 in each group while estimating a drop-out rate of 25%. Patients in the intervention group received special counseling sessions by the community pharmacist whereas those in the control group received the usual pharmacy services for six months. Pre-validated tool hypertension knowledge level scale was used to assess disease knowledge. The questionnaire was administered by the pharmacists to the respondents at baseline and after 6 months. Data was cleaned, coded and analyzed in SPSS 21. Results: The results of the present study showed that respondents having hypertension since the past one year had comparatively better knowledge (23.83, ±0.40) after six months of counseling. Mean knowledge scores regarding hypertension among intervention group at baseline was (15.60, ±3.33) which was improved after six months (18.35, ±2.31). The systolic and diastolic blood pressure also improved in intervention group after 6 months of counseling. Significant difference was observed (p≤0.05) in pre-post intervention knowledge regarding hypertension management. Knowledge of patients was improved regarding different aspects of hypertension management after counseling by community pharmacists. Conclusion: The results of the current study concluded that counseling by community pharmacist had a positive impact on hypertension management. Educational programs should be initiated by community pharmacists as this can lead to improvement in blood pressure goals, disease knowledge and medication adherence and enhance the image of pharmacist as a key health care member in management of chronic diseases.